A memória dos objetos: verônicas, máscaras e flores da Festa do Divino de Pirenópolis/Goiás - Geraldes, Amanda Alexandre Ferreira (2015)
The Feast of the Divine Holy Spirit in the city of Pirenópolis, in the state of Goiás (Brazil), occupies a special place in the collective imaginary of the community. The research sought to understand how and why this space was occupied, what is your singularity and how it was - and still is today - the process of this memory s construction. The research aims to analyze objects of material culture produced for the Feast and seeks to identify the relation between the meanings of the symbols and their representations in the collectivity of the community. The ritual objects chosen for this study are the verônicas of alfenim and the paper masks and flowers. The verônica is a gift from the Divine Empire and is associated with the devotional practices of popular religiosity. The masks and flowers express the popular culture in comic and festive irreverence of his masked ones. Therefore, we believe that knowledges, arts of making and the tradition are supported by a memory and builds collective and individual identities. We understand that the Feast merges with the history of the city, the family history and with the life history of the individual. The Feast causes great movement and popular involvement, and, more than that, a family involvement that supports the duty networks. The devotion to the Divine and the experience in the Feast are part of the very essence of the individual, the constitution of his identity, his memory, his life